The Role of Imperial Soldiers of Surakarta in Millennial Era - Hary Murcahyanto; Dewi Kusumaningsih; M. Adib Nazri (AMCA Journal of Community Development, 2024)
The paper is the research result that aims to describe in more detail the role of Imperial Soldiers and their participation in the current era. The research was conducted inside and outside the Surakarta Palace area through an ethnographic approach. The data of information was gained from the informants, direct observation, and documentation through the recording technique. For data collection, the researcher used interviews, observation, and documentation with interactive analysis. The core of this paper is the reality of the role of Imperial Soldiers Surakarta in guiding and keeping the good attitude inside the Surakarta Palace and showing it outside the Surakarta Palace as a model for society. The research has aspects that are studied and gained for the first time. As one of the informal education, Surakarta Palace has proven that It can organize the educational process in form of attitude and behavior so that every soldier could dedicate themselves for the sake of society and generally for the nation. Sumpah Prasetya Imperial Soldiers became the pioneer of the Indonesian national army vow. On-command Imperial Soldiers as the basic command that is used nationally. This fact showed that the activities of Imperial Soldiers in the form of social and cultural activities are an invaluable contribution.